Eight year longitudinal study of cataract surgeries in an urban Indian population - Nadkarni, Snehal; Patil, Priti; Roy, Nobhojit; Gerdin, Martin; Bhandarkar, Prashant (International Journal Of Community Medicine And Public Health, 2019)
Background: The aim was to study cataract surgery incidence in an urban community of 100,000 peoples in Mumbai. Methods: A retrospective observational community based study was performed for the period from January 01, 2008 to December 31, 2015. Electronic patient records were used to track surgeries performed in the members of community. Mid-year community census was considered as baseline population to estimate gender specific and age specific incidence of cataract surgery. Logistic regression was performed assuming gender and age-group as independent variables. Results: The rate of cataract extraction surgery varies from 786 to 952 surgeries per 100,000 per year. 6971 cataract surgeries were recorded with an overall average of 872/100,000/years. Increase in age was strongly associated with increase in incidence of cataract surgery and peak incidence was recorded for age group of 66–70 years. The odds of having surgery were similar in females and males 1.012 (95% CI 0.952 - 1.077). Conclusions: This study documented the rate of 872 cataract surgeries per year in an Indian population over eight years. Average incidence is found in the similar range of studies published from United States and Sweden. This community-based estimates of cataract surgery are useful for planning and managing resources at the national level.